Manpower planning: key to effective human resources development - Hamilton, Alexander (New York: Alexander Hamilton Institute, Inc., 1982)
This manual provides you with a foundation upon which you can erect a manpower planning system that will meet the special requirements of your company.
rpm 04/02/2019
Loans
Keywords: Human Resources Development